Integration of Learning Design and Evaluation in the Implementation of Kurikulum Merdeka: Evidence from Public Junior High Schools in Banjarmasin - Sovia Husni Rahmia; Mutiani Mutiani; Fatwa Nuraini; Sigit Triyono; Syarifuddin Syarifuddin (The Kalimantan Social Studies Journal, 2025)
The transition towards the Kurikulum Merdeka in Indonesia requires more adaptive and student-centered teaching practices, particularly in ensuring coherence between learning design and learning evaluation. This study aims to analyze the integration between learning design and evaluation in the implementation of the Kurikulum Merdeka in Social Studies classrooms. A descriptive qualitative approach was employed, involving 16 public junior high schools selected through random sampling. Data were collected through interviews, observations, and document analysis, and were subsequently analyzed using data reduction, data display, and conclusion-drawing techniques. The findings reveal that the process of learning design begins with a collaborative review of the Learning Outcomes (CP) through the Social Studies Teacher Forum (MGMP), followed by the development of the Learning Objectives Flow (ATP), diagnostic assessments, formulation of specific learning goals, and preparation of teaching modules. Learning evaluation consists of diagnostic, formative, and summative assessments, conducted with the aid of teaching module guidelines, attitude rubrics, digital assessment applications, and summative evaluation instruments. Integration is demonstrated through the alignment of objectives, learning activities, and evaluation criteria, as well as the use of assessment results to refine subsequent learning designs.This study concludes that effective integration between learning design and evaluation fosters adaptive and continuous improvement in teaching practices, consistent with the core principles of the Kurikulum Merdeka. The practical implications highlight the importance of optimizing MGMP as collaborative spaces for teachers, strengthening school support for integrated assessment systems, and enhancing teacher training programs on the development of teaching modules and sustainable assessment practices.